Socio-Economic Analysis and Incidence of Sexually Transmitted Infections in North Sumatra Province - samsul askhori (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
Introduction: Until now, Sexually Transmitted Infections (STIs) are still a health problem in the world, both developed and developing countries continue to strive to face and find solutions to overcome this disease, although prevention efforts carried out in various countries do not seem to have yielded satisfactory results. The purpose of this study was to analyze the determinants of sexually transmitted infections (STIs) based on data from the 2017 North Sumatra IDHS. Method: This type of research is an observational analytic study using a cross-sectional study design based on data from the 2017 North Sumatra Province IDHS. The population of this study was women aged 15-49 years who have had sexual relations. After cleaning the data, 1728 samples were included in the study. The data analysis technique used the frequency distribution of categorical variables, the analysis of the relationship between the independent variable and the dependent variable used the chi-square test, then the multivariate analysis used logistic regression test. Result : The results showed that the prevalence of sexually transmitted infections among women of childbearing age in North Sumatra was 25% (95% CI = 23.7% - 27.7%). The results showed that there was a significant relationship between age, education level and area of residence with the incidence of sexually transmitted infections (STIs). Then the multivariate analysis showed that the area of residence variable was the most dominant risk factor in causing the incidence of sexually transmitted infections (STIs). It is hoped that the government can overcome the problem of STIs through interventions on risk factors by providing education related to STIs in the community, especially women of childbearing age.